The Importance of Pleasure in the Moral for Kant's Ethics. Issue 2 (June 2016) - Holberg, Erica A.
ABSTRACT: I argue for a new reading of Kant's claim that respect is the moral incentive; this reading accommodates the central insights of the affectivist and intellectualist readings of respect, while avoiding shortcomings of each. I show that within Kant's ethical system, the feeling of respect should be understood as paradigmatic of a kind of pleasure, pleasure in the moral. The motivational power of respect arises from its nature as pleasurable feeling, but the feeling does not directly motivate individual dutiful actions. Rather, the feeling is motivational in the sense that, after an agent has acted in a morally good way, the pleasure that results from that action contributes to the cultivation of virtue in the agent and, consequently, morally good actions in the future. Understanding the feeling of respect to be moral pleasure not only gives us insight into how finite rational beings develop virtue, but also a new way of understanding respect as an incentive.